2020
DOI: 10.1002/ar.24417
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of structure and gene expression in developing kidneys of male and female rats exposed to low protein diets in utero

Abstract: A maternal low protein (LP) diet in rodents often results in low nephron endowment and renal pathophysiology in adult life, with outcomes often differing between male and female offspring. Precisely how a maternal LP diet results in low nephron endowment is unknown. We conducted morphological and molecular studies of branching morphogenesis and nephrogenesis to identify mechanisms and timepoints that might give rise to low nephron endowment. Sprague–Dawley rats were fed a normal protein (19.4% protein, NP) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(63 reference statements)
0
4
2
Order By: Relevance
“…In these models of maternal food restriction, the maternal body weight and thus leptin were reduced, suggesting that leptin may regulate branching morphogenesis via a Gdnf /Ret pathway. Of interest, a previous study has shown that there are sex-specific differences in Gdnf in mice [33], which was not observed in our study in rats. Furthermore, in this study in mice, a maternal low-protein diet did not alter Gdnf mRNA [33].…”
Section: Discussioncontrasting
confidence: 87%
“…In these models of maternal food restriction, the maternal body weight and thus leptin were reduced, suggesting that leptin may regulate branching morphogenesis via a Gdnf /Ret pathway. Of interest, a previous study has shown that there are sex-specific differences in Gdnf in mice [33], which was not observed in our study in rats. Furthermore, in this study in mice, a maternal low-protein diet did not alter Gdnf mRNA [33].…”
Section: Discussioncontrasting
confidence: 87%
“…45 This statistical method has been used by various investigators to account for the potential within-litter bias. [46][47][48][49][50][51][52][53] This statistical analysis was used to reduce confounding due to over-representation of a particular litter in the data. Therefore, herein we report findings from an n (litter) of 4-18, which represents between 2 and 79 animals.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study exploring the impact of maternal protein intake during gestation revealed that at E20 LP offspring were heavier than control offspring. 53 It is unclear whether this result is indicative of a change in gestational length. Therefore, future studies may wish to further explore the role of maternal protein intake on gestational length.…”
Section: Limitation Of Studymentioning
confidence: 99%
“…In a rabbit model of maternal hypertension, Monash colleague and collaborator Prof. Kate Denton describes methodologies for the in utero high‐resolution ultrasound assessment of fetal growth trajectories, including helpful assessments of fetal kidney size (Coombs, Walton, Maduwegedera, Flower, & Denton, 2020). Additionally, in a study of maternal low protein diet in rats, collaborator Prof. James Armitage and former PhD student Dr. Ryan Wood‐Bradley add insight to the mechanisms underlying low nephron endowment in affected offspring, showing molecular and structural changes in the fetal kidneys from embryonic day E17.25 (Wood‐Bradley et al, 2020). Notably, members of John's current research team, including research fellow Dr. Luise Cullen‐McEwen, present in this issue the first reported evidence of developmental programming of podocyte endowment (Gonçalves et al, 2020); in a mouse model of maternal hypoxia, low podocyte (and nephron) numbers were evident in male, but not female, offspring, further indicating that renal disease susceptibility may be sex‐specific.…”
Section: Renal Developmental Programmingmentioning
confidence: 99%